2018
DOI: 10.1038/s41598-018-29467-7
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and years of life lost due to breast cancer attributable to physical inactivity in the Brazilian female population (1990–2015)

Abstract: The aims of this study were as follows: to estimate the mortality and years of life lost, assessed by disability-adjusted life years (DALYs), due to breast cancer attributable to physical inactivity in Brazilian women; to compare the estimates attributable to physical inactivity and to other modifiable risk factors; and to analyse the temporal evolution of these estimates within Brazilian states over 25 years (1990–2015), compared with global estimates. Databases from the Global Burden of Disease Study for Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 39 publications
1
19
0
2
Order By: Relevance
“…: 45.52-60.30) in 1990 to 74.02 (95% U.I. : 61.90-85.86) in 2015 [7]. While breast cancer incidence has increased in Brazil, there have been conflicting reports as to if breast cancer mortality has remained stable [7][8][9] or increased [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…: 45.52-60.30) in 1990 to 74.02 (95% U.I. : 61.90-85.86) in 2015 [7]. While breast cancer incidence has increased in Brazil, there have been conflicting reports as to if breast cancer mortality has remained stable [7][8][9] or increased [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…: 61.90-85.86) in 2015 [7]. While breast cancer incidence has increased in Brazil, there have been conflicting reports as to if breast cancer mortality has remained stable [7][8][9] or increased [10][11][12][13][14]. However, all studies have shown regional disparities in breast cancer mortality in the Brazilian regions, usually with rates remaining stable or declining in more developed regions and increasing in less developed regions [6,8,10,11,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Excess circulating hormones are present, particularly estrogen, which causes the development of carcinogenesis and mutations by prompting free-radical production, revealing genotoxicity. Hyperinsulinemia is another factor causing breast cancer, which encourages insulin-like growth factor (IGF-1) production and activity [37]. Therefore, increased accumulation of estrogen and IGF-1 contributes to breast cancer development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…An analytical study based on estimates of global burden of disease for Brazil made by GBD 2017 was carried out, coordinated by the Institute for Health Metrics and Evaluation (IHME) in partnership with the Ministry of Health of Brazil [11][12][13][14][15]. In the analysis of mortality, information from the Mortality Information System of the Brazilian Ministry of Health was used, with adjustment for underreporting of deaths and declaration of undefined/nonspecific causes, called garbage codes [13][14][15].…”
Section: General Aspectsmentioning
confidence: 99%